Developing Social Sensitivity Through Prophetic Parenting Psychoeducation: A Contextual Teaching and Learning Approach in Islamic Boarding Schools - Hamidah, Iim Imas; Falah, Falasifatul; Warizki, Viyanita Nur Putri Eka; Putra, Septian Prawisuda (Universitas Muhammadiyah Yogyakarta, 2025)
Social sensitivity is a fundamental competency for harmonious communal living and the realization of Islamic social ethics. One of the causes of problematic behaviors among Islamic boarding school (pesantren) students in the post-COVID-19 period, such as bullying, was the decline in students' social sensitivity. This study aimed to examine the effectiveness, durability, and qualitative behavioral impact of a Prophetic Parenting Psychoeducation program delivered through a Contextual Teaching and Learning (CTL) approach on social sensitivity among pesantren students. The measuring instrument used was a Social Sensitivity Scale developed by Bozdağ and Bozdağ (2021), adapted for the Indonesian pesantren context, with a Cronbach's Alpha reliability coefficient of 0.815. This study used a mixed-methods approach with a sequential explanatory design in which a quasi-experiment was carried out, followed by a qualitative study. The sample was selected with a purposive sampling technique, involving students aged 12 to 18 with low to moderate levels of social sensitivity. A total of 40 students were divided into 20 in the experimental group and 20 in the control group. Data analysis used a paired sample t-test and the N-Gain effectiveness test, supplemented by thematic analysis of qualitative data. The results showed that the prophetic parenting psychoeducation intervention through the CTL approach significantly increased the social sensitivity of post-COVID-19 pesantren students in the experimental group compared to the control group, with effectiveness in the moderate category. Qualitative findings revealed behavioral changes across four interconnected domains: empathic awareness, prosocial responsibility, cognitive flexibility, and respectful social interaction. This result supports the role of the CTL approach in educational psychology and the application of prophetic parenting values in Islamic education to increase adolescents' social sensitivity.